2004
DOI: 10.1097/01.mlg.000148224.83491.0f
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Respiratory Papillomatosis: A Longitudinal Study Comparing Severity Associated With Human Papilloma Viral Types 6 and 11 and Other Risk Factors in a Large Pediatric Population

Abstract: Statistical analysis of the relationships among epidemiological factors, HPV type, and clinical course revealed that patients with HPV-11 and patients younger than 3 years of age at RRP diagnosis are prone to develop more aggressive disease as represented by higher severity scores at endoscopic debridement, more frequent operative debridement procedures per year, a greater requirement for adjuvant therapy, and greater likelihood of tracheal disease with tracheotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
184
4
27

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(228 citation statements)
references
References 102 publications
13
184
4
27
Order By: Relevance
“…Conversely, late (adult) onset RRP may be more likely than juvenile RRP to retain features of the productive HPV phenotype, which may also contribute to adult lesion recurrence. Previous studies have shown HPV 11 to be associated with a more aggressive clinical course in children, including development of tracheal disease, pulmonary disease, and greater frequency of surgical procedures including tracheotomies [20][21][22]. However, HPV 11 was not demonstrated to be a significant biomarker of recurrence or dysplasia in juveniles in this study: only 28.6% of juveniles with recurrent papillomas, and only 40% of those with C1 dysplastic papilloma were positive for HPV 11.…”
Section: Discussioncontrasting
confidence: 77%
“…Conversely, late (adult) onset RRP may be more likely than juvenile RRP to retain features of the productive HPV phenotype, which may also contribute to adult lesion recurrence. Previous studies have shown HPV 11 to be associated with a more aggressive clinical course in children, including development of tracheal disease, pulmonary disease, and greater frequency of surgical procedures including tracheotomies [20][21][22]. However, HPV 11 was not demonstrated to be a significant biomarker of recurrence or dysplasia in juveniles in this study: only 28.6% of juveniles with recurrent papillomas, and only 40% of those with C1 dysplastic papilloma were positive for HPV 11.…”
Section: Discussioncontrasting
confidence: 77%
“…Such papillomas pose a threat to the patient's health and life, and may undergo oncogenic transformation. Cases of total remission have been reported (33), and papillomas that are due to HPV11 infection are more severe (39).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Anogenital warts are also caused by low-risk HPV types 6 and 11. High-risk HPV types cause precancers and cancer of the penis and anus.…”
mentioning
confidence: 99%
“…5 The low-risk types of HPV cause recurrent respiratory papillomatosis or condylomata of the nasopharynx. 6,7 Anogenital warts are also caused by low-risk HPV types 6 and 11. High-risk HPV types cause precancers and cancer of the penis and anus.…”
mentioning
confidence: 99%